Subaltern Voices and Survivor Empowerment: A Spivakian Feminist Study of Sexual Violence in the Save Your Mental Community - Damayanti, Titik; Muhammad Riduan Harahap; Irwansyah, Irwansyah (Faculty of Ushuluddin and Philosophy, 2024)
The phenomenon of sexual violence in Indonesia requires special attention, given its nearly uniform prevalence across all provinces. This study aims to analyze the experiences of sexual violence survivors within the Save Your Mental (SYM) community using Gayatri Spivak’s feminist approach. The method employed is qualitative-descriptive, with data collected through interviews and observations of the community founder, Romayana Sari, and two community members. Data were analyzed using Spivak’s subaltern theory to understand the dynamics of marginalization, discrimination, and social construction experienced by survivors. The results of the study indicate that sexual violence, mental health disorders, and bullying are the main issues faced by SYM members. These findings show how the community supports the trauma recovery process and rebuilding survivors’ self-confidence. This study also recommends further exploring other members’ experiences and using alternative theories to enrich the analysis and provide contextually relevant solutions for victims. Thus, this research contributes to efforts to strengthen understanding of sexual violence experiences and the importance of empowering survivors through a humanistic and critical approach.